Law Enforcement Against Transnational Cybercrime:Jurisdictional Problems and Regulatory Harmonization - Rahmatilah Rahmatilah (PT. Anagata Sembagi Education, 2026)
The rapid development of information and communication technology has given rise to the phenomenon of transnational cybercrime, which challenges conventional criminal law, particularly the doctrine of territorial jurisdiction. This article aims to critically analyze the jurisdictional issues in law enforcement against transnational cybercrime and the urgency of regulatory harmonization at the global and regional levels. Using normative legal research methods based on statute, comparative, and conceptual approaches, this study finds that jurisdictional conflicts between countries constitute a structural obstacle stemming from the incompatibility between the concept of territorial state sovereignty and the borderless nature of cybercrime. Furthermore, harmonization efforts through the Budapest Convention have not achieved universal acceptability due to resistance from developing countries that view it as a Western instrument. Indonesia, as a country with high internet penetration, faces a dual challenge: limited domestic regulations and the absence of ratification of relevant international legal instruments. This study concludes that effective law enforcement against transnational cybercrime necessitates reform of international criminal law through an inclusive multilateral approach, strengthening of mutual legal assistance mechanisms, and transforming the jurisdictional paradigm from the principle of territoriality to the contextual effects doctrine principle.